Protective effects of dietary restriction and physical exercise on intrahepatic fat accumulation - Yuka Kurosaka; Hideki Yamauchi; Shigeru Takemori; Kumiko Minato (Japanese Society of Physical Fitness and Sports Medicine, 2018)
This paper discusses the effects of dietary restriction and physical exercise on the maintenance of good health, focusing on intrahepatic fat accumulation, a type of ectopic fat accumulation. Excessive intrahepatic fat accumulation eventually progresses to fatty liver, which may evolve into liver cirrhosis and liver cancer. Physical exercise and dietary restriction are generally accepted as the major non-pharmacological remedies against intrahepatic fat accumulation. However, a combination of diet and physical activity has not necessarily shown expected synergistic or additive effects. In fact, dietary conditions antagonistically blocked the effect of physical activity on fatty liver, and physical inactivity adversely exacerbated the effect of dietary restriction on intrahepatic fat accumulation. These diverse combination effects, as well as etiology-dependent diversity in the activation of cellular signaling pathways leading to fatty liver, suggest the need to optimize remedies for the efficient amelioration and prevention of intrahepatic fat accumulation in a case-dependent manner. As a tentative step to constructing a prescription formula for optimal remedies, the probable advantage of physical exercise over dietary restriction at preventing fat spillover from adipose tissue to liver is noted.